PENERAPAN MODEL KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR HIWAR DI MAS PLUS PADANG GANTING - Hardison, Hardison (Lughawiyah: Journal of Arabic Education and Linguistics, 2019)
This study aims to describe students’ activities and their learning outcomes using make a match type of cooperative learning model in learning hiwar. This research is a classroom action research consisting of two cycles. Each cycle consists of planning, action, observation and reflection. Data were collected through observation and then analyzed by using descriptive qualitative technique. The results of the data analysis indicate that make a match type can increase the activity and learning achievement of class X MAS Plus Padang Ganting students. The relevancy of students’ activities and learning activities in cycle II is increased for about 23.11%, and the unrelevancy of students’ activities and learning activities is decreased for about 16.26% in cycle II. While, students’ understanding about hiwar is increased 13.33%, and learning completeness is also increased 20.86% in cycle II.